Pengaruh Model Pembelajaran Cooperative Script Terhadap Kemampuan Komunikasi Matematis Pada Siswa Kelas IV SD N 1 Blang Mangat - Mawar Agustina; Bahri, Samsul; Misrina (Genderang Asa: Journal of Primary Education, 2024)
The mathematical communication skills of elementary school students in mathematics are still low. In the learning process students have difficulty explaining and completing the material that has been taught by the teacher. The purpose of this study was to determine the effect of the Cooperative Script learning model on the mathematical communication skills of fourth grade students at SDN 1 Blang Mangat. This study used a quantitative approach, with a Quasi-Experimental type, the population in this study were all fourth grade students at SDN 1 Blang Mangat, totaling 51 students. Withdrawal of this research sample using total sampling technique. In this study, the experimental class was class IV A with a total of 26 students, and the control class was class IV B with a total of 25 students. Data collection techniques used instruments in the form of pre-tests and post-tests which totaled 5 fractional questions in the form of descriptions. The results of data analysis using SPSS version 22, hypothesis testing using the Mann Whitney test. Based on the results of the final analysis using the Mann Whitney test, an Asymp Sig value of 0.708 was obtained at a significance level of 0.05. Asymp Sig = 0.708 > 0.05 then Ha is rejected and Ho is accepted, thus this study can be concluded that there is no effect of the cooperative script learning model on mathematical communication skills in fourth grade students of SDN 1 Blang Mangat. The cause of the hypothesis has no effect, namely the indicators on mathematical communication skills are not met as a whole.